Inflammatory biomarkers and cerebral small vessel disease: a community-based cohort study. Issue 4 (8th March 2022) - Zhang, Ding-Ding; Cao, Yuan; Mu, Jing-Yu; Liu, Yi-Ming; Gao, Feng; Han, Fei; Zhai, Fei-Fei; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Li, Ming-Li; Jin, Zheng-Yu; et al.
Abstract : Background and purpose: Although inflammation has been proposed to be a candidate risk factor for cerebral small vessel disease (CSVD), previous findings remain largely inconclusive and vary according to disease status and study designs. The present study aimed to investigate possible associations between inflammatory biomarkers and MRI markers of CSVD. Methods: A group of 15 serum inflammatory biomarkers representing a variety of those putatively involved in the inflammatory cascade was grouped and assessed in a cross-sectional study involving 960 stroke-free subjects. The biomarker panel was grouped as follows: systemic inflammation (high-sensitivity C reactive protein (hsCRP), interleukin 6 and tumour necrosis factor α), endothelial-related inflammation (E-selectin, P-selectin, intercellular adhesion molecule 1, vascular cell adhesion molecule 1 (VCAM-1), CD40 ligand, lipoprotein-associated phospholipase A2, chitinase-3-like-1 protein and total homocysteine (tHCY)) and media-related inflammation (matrix metalloproteinases 2, 3 and 9, and osteopontin). The association(s) between different inflammatory groups and white matter hyperintensity (WMH), lacunes, cerebral microbleeds (CMBs), enlarged perivascular space (PVS) and the number of deep medullary veins (DMVs) were investigated. Results: High levels of serum endothelial-related inflammatory biomarkers were associated with both increased WMH volume (R 2 =0.435, p=0.015) and the presence of lacunes (R 2 =0.254, p=0.027). Backward stepwise elimination of individual inflammatory biomarkers for endothelial-related biomarkers revealed that VCAM-1 was significant for WMH (β=0.063, p=0.005) and tHCY was significant for lacunes (β=0.069, p<0.001). There was no association between any group of inflammatory biomarkers and CMBs or PVS. Systemic inflammatory biomarkers were associated with fewer DMVs (R 2 =0.032, p=0.006), and backward stepwise elimination of individual systemic-related inflammatory biomarkers revealed that hsCRP (β=−0.162, p=0.007) was significant. Conclusion: WMH and lacunes were associated with endothelial-related inflammatory biomarkers, and fewer DMVs were associated with systemic inflammation, thus suggesting different underlying inflammatory processes and mechanisms.